Prevalence Pattern of Cancer and Handling of Cytotoxic Drugs - Bajracharya, Nishma; Karki, Pratima; Sapkota, Sujata; Bastakoti, Sharmila; Yagol, Niva; Khan, G.M.; Shakya, Rajani; Rao, B.S. (Kathmandu University Journal of Science, Engineering and Technology, 2006)
A retrospective study was conducted in two hospitals, namely Bhaktapur Cancer Care Center and Om Hospital and Research Center, focusing on the prevalence pattern, management of cancer, and handling of cytotoxic drugs. A total of 358 cancer cases (179 from each hospital) were analyzed. Questionnaires were utilized to assess the handling of cytotoxic drugs in the hospitals. The study revealed that individuals in the age group of 45-65 were more susceptible to cancer. The top five malignancies identified were stomach, ovarian, Non-Hodgkin’s Lymphoma (NHL), lung, and breast cancer. Females exhibited a higher incidence of cancer compared to males, with the female reproductive system and breast being the most prevalent sites. Assessment of cytotoxic drug management was conducted by reviewing the medical records of in-patients receiving chemotherapy, revealing rational drug therapy prescriptions for all cancer cases in both hospitals. Handling of cytotoxic drugs was evaluated through direct observation of reconstitution and administration procedures, administration questionnaires, and interviews with medical personnel. Inadequate knowledge, insufficient training of personnel, limited financial resources, inadequate handling equipment, and increased risk of accidents and spills were identified as contributing factors to inappropriate drug handling practices.